Miniaturised wideband bandpass filter based on harmonic suppressed dual transmission lines. Issue 9 (4th April 2016) - Zhang, Bo; Wu, Yongle; Yu, Cuiping; Liu, Yuanan
Abstract : A novel miniaturised wideband bandpass filter (BPF) based on harmonic suppressed dual transmission lines (DTLs) is introduced with enhanced upper stopband rejection and passaband selectivity. The transmission and harmonic suppression characteristics of series and parallel connected DTLs are analysed adopting even–odd mode method. To verify the proposed structure, a high selective wideband BPF centred at 1.86 GHz with a fractional bandwidth of 93.5% is designed and fabricated. The upper stopband is extended up to 8.8 GHz (4.7 f 0 ) with the suppression level of above 35 dB. Furthermore, a size reduction of 30% can be achieved in proposed BPF, compared with conventional wideband BPF based on quarter‐wavelength transmission lines.